Impacts of Dislocations on the Anisotropic Etching of Ge/Si for Suspended Ge Membrane. (1st January 2016) - Chen, Chaowen; Lin, Guangyang; Lan, Xiaoling; Chen, Ningli; Li, Cheng; Chen, Songyan; Huang, Wei; Lai, Hongkai
Abstract : The impacts of dislocations in Ge on Si substrate on the anisotropic TMAH wet etching from back side for suspended Ge membrane were investigated. It was found that the dislocation-rich regions near the interface between Ge and Si induced by the large lattice mismatch between Si and Ge have significant effect on the etching process. The etch pits were generated on the bottom of windows when the etch depth reached near the dislocation regions from the back side. The etch pits were then enlarged following the no mask etching rule of Wulff-Jaccodine's method and finally penetrated into the Ge surface, which made it possible to crack the Ge membrane. The suspended Ge/Si bilayer structures were made with various window sizes and the influence of etch pits and window sizes on tensile strain in Ge membranes were discussed.